AYURVEDIC MANAGEMENT OF GRIDHRASI W. S. R. SCIATICA: A CASE STUDY - Doke, Sagar Yashwant; Pathade, Chandrakant N. (International Journal of Research -GRANTHAALAYAH, 2018)
Gridhrasi is one of the “Nanatmaja Vyadhis of vata”. Improper sitting postures continuous and over exertion, jerking movements during travelling and sports produce structural abnormality in spinal cord. Vata is the prime dosha in the causation of Gridhrasi. The vitiated vata dosha get localized in the sphik, kati region. Occasionally it will be associated with kapha producing vata kaphaj Gridhrasi. Gridhrasi is shoolpradhan vyadhi so it causes great discomfort to the patient. Pain primarily starts in the sphik region and in kati which can be related to lumbosacral region where sciatic nerve root starts. Pain later radiates through the posterior aspect of uru, janu, jangha, pada. Gridrasi is cured by the help of shamana chikitsa. Hence in the case study of male patient of age 48 yrs presenting with cardinal clinical sign and symptoms of Gridhrasi are Ruka, Toda, Stambha and Muhu Spandana in the Sphika, Kati, Uru,Janu, Jangha and Pad in order and Sakthikshepanigraha that is restricted lifting of the leg.